2003
DOI: 10.1007/s00405-002-0519-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the early auditory effects of hyperlipoproteinemia and diabetes mellitus using otoacoustic emissions

Abstract: Although the relationship between hearing loss and hyperlipoproteinemia (HLP) or diabetes mellitus (DM) has been shown in many clinical investigations, this concept is still controversial. A prospective study was designed to search for the existence of subclinical auditory dysfunction related to HLP and DM by transient-evoked (TEOAEs) and distortion-product otoacoustic emissions (DPOAEs) in patients with hearing levels better than 30 dB. Evoked otoacoustic emissions were utilized to investigate subclinical aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 36 publications
(48 reference statements)
3
8
0
Order By: Relevance
“…Cochlear deterioration may be caused by metabolic diseases, such as hyperlipoproteinemia, and DM has been reported to cause changes in DPOAE amplitudes. 25,46 In our study, the mean DPOAE amplitudes were low in the diabetic rats and increased in a dose-dependent manner with PTS treatment. These data indicate that PTS may protect the outer hair cells, a finding that is consistent with our histopathological, immunohistochemical, and molecular findings, which all demonstrated decreased cochlear damage related to DM.…”
Section: Discussionsupporting
confidence: 44%
“…Cochlear deterioration may be caused by metabolic diseases, such as hyperlipoproteinemia, and DM has been reported to cause changes in DPOAE amplitudes. 25,46 In our study, the mean DPOAE amplitudes were low in the diabetic rats and increased in a dose-dependent manner with PTS treatment. These data indicate that PTS may protect the outer hair cells, a finding that is consistent with our histopathological, immunohistochemical, and molecular findings, which all demonstrated decreased cochlear damage related to DM.…”
Section: Discussionsupporting
confidence: 44%
“…It is clinically beneficial in revealing early cochlear damage even in patients with normal hearing. Using DPOAE and TEOAE, Erdem T et al showed that hyperlipoproteinemia and diabetes mellitus result in cochlear pathology affecting outer hair cells in patients with normal hearing (7). In this paper, we evaluated the pathological effects of HT on the cochlea by pure tone audiometry and DPOAE in patients without any clinical hearing loss.…”
Section: Table 3: Comparison Of Distortion Product Otoacoustic Emissimentioning
confidence: 99%
“…A close interrelation between hearing loss and high serum cholesterol levels is shown in several studies, and the dependence of hearing function on some other atherogenic lipid levels in the blood is found. Inverse correlation of high significance between high-density lipoproteins (HDL) level of the peripheral blood and hearing acuity at the frequency of 4 kHz was revealed [22]. Morphological and functional damages of the cochlea and their correlations with hyperlipidemia, atherosclerosis, and endothelial dysfunction in mice are described in studies of Guo et al [23].…”
Section: Introductionmentioning
confidence: 99%